Park w dobie obrazów cyfrowych. Praktyki późnej nowoczesności: bywać – naturalizować – mieszkać - Banaszkiewicz, Karina (Śląskie Studia Polonistyczne, 2018)
Park as an intentionally formed phenomenon is an example of imposing on reality both anthropocentric patterns and those typical of a specific cultural context. Interpreted against the backdrop of space, nature, landscape, it unravels its power as a human gesture, sign and measure of human nature – expresses a man’s attitude to the world. Founded on the topographical experience, a park gains the status of a place and initiates the processes of taming and naturalization. Everyday being with a park leads to living, which then endows a park with an order of life and identity. To be, to naturalize, to live – these are the practices of existence in the world, deconstructed by the processes of globalisation, including digitalization. While analysing digital realizations of a park and a park extended over the spaces emitted by the screens and monitors of digital devices in terms of the functions it performs in a modern and postmodern city, this paper asks about contemporary forms of settlement, embodied by virtual and real parks.